Management of wet bubble disease (Mycogone perniciosa ) in Agaricus bisporus - Sharma, V P; Kumar, Satish; Kamal, Shwet (Mushroom Research, 2018)
Wet bubble disease incited by Mycogone perniciosa Magn. in white button mushroom (Agaricus bisporus)  is a serious pathogen inflicts heavy damage to the crop, various attempts have been made to manage the disease through various means. Present study in intended to study the interaction of host and pathogen and control measures to reduce the crop losses in button mushroom. Interaction studies between A. bisporus and M. perniciosa conducted in dual, half plate and paired cultures.  The average growth of A. bisporus and M. perniciosa in either dual culture was 16.13 and 28.86 mm, respectively. Growth of A. bisporus remain unaffected (16.02 mm) and Mycogone enhanced to 36.91mm (21.80% increase) when both grown in dual culture. Pre spawning of casing soil with A. bisporus spawn, 5-20 days prior to pasteurization resulted in reduced incidence of wet bubble disease. Thermal death point of Mycogone observed to be at 44-45°C. Moisture contents of casing soil less than 60% at the time of pasteurization favour the survival of M. perniciosa. Mycogone failed to survive in casing soil having moisture contents 60% or above at 60°C or above temperature. Two bacterial isolates B-9 (Bacillus) and B-18 (Alcaligenes) proved to be very promising bio control agents for the management of wet bubble disease both under laboratory and mushroom house conditions. Out of five fungicides and two other chemicals tried, carbendazim proved most effective in managing wet bubble disease among all the fungicides/ chemical tested.